2007
DOI: 10.1016/j.cell.2007.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Local and cis Effects of the H Element on Expression of Odorant Receptor Genes in Mouse

Abstract: From the approximately 1,200 odorant receptor (OR) genes in the mouse genome, an olfactory sensory neuron is thought to express only one gene. The mechanisms of OR gene choice are not understood. A 2.1 kilobase region (the H element) adjacent to a cluster of seven OR genes has been proposed as a trans- and pan-enhancer for OR gene expression. Here, we deleted the H element by gene targeting in mice. The deletion abolishes expression of a family of three OR genes proximal to H, and H operates in cis on these ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
163
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(170 citation statements)
references
References 41 publications
(88 reference statements)
4
163
1
2
Order By: Relevance
“…This result lends support to the second and/or third possibility, but further experiments will be required to distinguish them. In addition to the mechanisms proposed in OR gene selection and stabilization (Fuss et al, 2007;Lewcock and Reed, 2004;Lomvardas et al, 2006;Nguyen et al, 2007;Serizawa et al, 2003;Shykind et al, 2004), the current study reveals an activity-dependent mechanism in ensuring and maintaining that one cell expresses only receptor in a subset of sensory neurons.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This result lends support to the second and/or third possibility, but further experiments will be required to distinguish them. In addition to the mechanisms proposed in OR gene selection and stabilization (Fuss et al, 2007;Lewcock and Reed, 2004;Lomvardas et al, 2006;Nguyen et al, 2007;Serizawa et al, 2003;Shykind et al, 2004), the current study reveals an activity-dependent mechanism in ensuring and maintaining that one cell expresses only receptor in a subset of sensory neurons.…”
Section: Discussionmentioning
confidence: 65%
“…The underlying mechanism is under extensive investigation and likely involves several hierarchical steps from the initial OR selection to silencing other ORs (Fuss et al, 2007;Lomvardas et al, 2006;Nguyen et al, 2007). It has been reported that stabilizing an OR choice in individual neurons requires a negative feedback triggered by the receptor protein, especially encoded by a functional OR gene (Lewcock and Reed, 2004;Serizawa et al, 2003;Shykind et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We have identified OR genes in other primates that have been lost from the human genome, and vice versa. In addition, it is possible that the fission event and subsequent structural changes have divorced these OR genes from their original regulatory context, which might have altered the relative expression of the intact genes, as expression of some OR genes is known to require interaction with an enhancer that lies up to 2 Mb away (Serizawa et al 2003;Fuss et al 2007). However, we showed previously that gene I is transcribed from multiple human subtelomeres report that OR genes D, E, F, G, and U are expressed in human olfactory epithelium (genes H-K were not included on their microarray used to assay expression in this tissue).…”
Section: Discussionmentioning
confidence: 99%
“…Each olfactory sensory neuron (OSN) in the main olfactory epithelium (MOE) most likely expresses a single OR gene, although the underlying mechanisms are not fully understood (Serizawa et al, 2003;Lewcock and Reed, 2004;Shykind et al, 2004;Lomvardas et al, 2006;Fuss et al, 2007). All OSNs expressing the same OR converge their axons onto one or a few specific glomeruli in the main olfactory bulb (Mombaerts, 2006).…”
Section: Introductionmentioning
confidence: 99%